Implementasi Pola Asuh Demokratis dalam Pembentukan Karakter Kejujuran Anak Usia Dini di Desa Sikapas Mandailing Natal - Nasution, Asrija Murni; P, Fuji Rahmadi (AS-SABIQUN, 2023)
Parental care is the main pillar in forming the character of honesty in young children. Democratic parenting is considered as parenting that is relevant and appropriate to be applied to young children who have changes in attitudes and daily activities. Suhuas Mandailing Natal Village is a village that is rich in culture and ethnicity. The culture that is owned will have an impact on the care provided by parents. The aim of this research is to determine the implementation of democratic parenting in forming the honest character of early childhood. The method used in this research is qualitative with data collection techniques using participant observation and in-depth interviews. All existing data is analyzed using the stages of data condensation, data display and verification. The findings in this research are that the democratic parenting pattern that is implemented for children is providing close attention and warmth to children, discussing every activity and rule that is applied to children consistently, providing a good example by getting used to saying and behaving well. Parents who implement democratic parenting will find it easier to instill the character value of honesty in their children. The formation of the character of honesty must start from the parents, children will observe and imitate the honest activities carried out by their parents throughout their lives.